2018
DOI: 10.1371/journal.pone.0193920
|View full text |Cite
|
Sign up to set email alerts
|

White blood cell subpopulation changes and prevalence of neutropenia among Arab diabetic patients attending Dasman Diabetes Institute in Kuwait

Abstract: BackgroundThe effects of diabetes mellitus on the differential white blood cell count are not widely studied in the Arab populations. The objective of this cross-sectional, retrospective study is to assess the influence of chronic diabetes mellitus on white blood cell counts, absolute neutrophil (ANC) and lymphocyte counts (ALC) as well as the prevalence of benign ethnic neutropenia among Arabs attending the Dasman Diabetes Institute (DDI) in Kuwait.Methods and findings1,580 out of 5,200 patients registered in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…The findings of the present study complement those of Whiskey and colleagues, where it was shown that only 8.4% of black patients who were treated with clozapine in one of the same care settings were registered with BEN [2]. While our findings indicate a twofold improvement in the recognition of BEN by clinicians in SLaM in recent years, our data reaffirms that BEN identification remains lower than the prevalence rates described in the literature suggesting a selection in practice [25].…”
Section: Comparison With Other Studiessupporting
confidence: 85%
“…The findings of the present study complement those of Whiskey and colleagues, where it was shown that only 8.4% of black patients who were treated with clozapine in one of the same care settings were registered with BEN [2]. While our findings indicate a twofold improvement in the recognition of BEN by clinicians in SLaM in recent years, our data reaffirms that BEN identification remains lower than the prevalence rates described in the literature suggesting a selection in practice [25].…”
Section: Comparison With Other Studiessupporting
confidence: 85%